Isolated Visceral Angioedema Induced by Angiotensin-Converting Enzyme Inhibitor - Oliveira, Ana Maria (GE Port J Gastroenterol, 2015)
Visceral angioedema is a rare complication of therapy with angiotensin-converting enzyme (ACE) inhibitors. Clinical presentation includes nausea, vomiting, abdominal pain and diarrhea. Early detection of this entity can prevent recurrent episodes and unnecessary invasive procedures, including surgery. This article describes a 46-year-old-woman who presented to the emergency department with abdominal pain, associated with nausea and vomiting. She had been taking ramipril for 15 days. A computed tomography was performed which revealed thickening of a jejunal segment, with submucosal edema. ACE inhibitor-associated angioedema was suspected and the medication was discontinued, with resolution of symptoms in 48 h. After 7 months of follow-up, the patient is asymptomatic. Despite of its rarity, ACE inhibitor-induced small-bowel angioedema should be included in the differential diagnosis when patients receiving ACE inhibitor therapy present with abdominal complaints.